Sustainable energy efficiency, greener energy and energy-related emissions nexus: Sustainability-related implications for G7 economies - Pi, Kai; Khan, Salahuddin; Raza, Syed Ali; Shahzadi, Irum [UNESP] (Wiley, 2024)
The topic of energy efficiency and environmental quality is quickly becoming one of the most pressing concerns facing the globe today. The linkage between energy efficiency and high environmental quality standards has significant repercussions for the long-term viability of the ecosystem. The prime objective of this study is to explore the nexus between sustainable energy efficiency, green energy and energy-related emissions. Energy efficiency has the potential to be a key tool in the pursuit of environmental sustainability. This study investigates the dynamic relationships between energy efficiency and energy-related greenhouse gases (GHG) in developed countries from 1990 to 2020. Using advanced econometric approaches, the results argue that energy efficiency, globalization and greener energy adoption are helpful for the reduction of GHG emissions in developed countries. Moreover, economic growth increases GHG emissions in developed countries. Furthermore, we find a bidirectional causality of energy-related greenhouse gas emissions with energy efficiency, income and globalization. The study results guide policymakers on the policies they can implement apropos greener energies and enforce to ensure sustainable development.
Keywords: developed economies; energy efficiency; energy-related emissions; greener energy; sustainable development